(untitled) (BIRDEM Medical Journal, 2020)
Norwegian scabies is characterized by hyperkeratotic, heavily scaling, crusted lesions rarely presents as exfoliative dermatitis (erythroderma). This term applies when 90% or more of the skin surface is involved by scabies. A 75-year-old woman having uncontrolled diabetes mellitus and hypertension was admitted in BIRDEM general hospital with generalized erythroderma for 6 months and high fever along with vomiting for 4 days. Clinical and laboratory findings were suggestive of severe sepsis with septic shock, which were being managed by supportive medications. Microscopic examination of scales and crusts dissolved in 10% KOH revealed fields teeming with scabies mites and eggs. A skin biopsy was planned but could not be done due to critical condition of the patient. Despite of all supportive measures, patient expired due to septic shock before starting definitive treatment of Norwegian scabies. Birdem Med J 2020; 10(3): 215-217